Studies on species of Holarctic Pardosa groups (Araneae, Lycosidae). VIII. The Palearctic species of the Pardosa nigra group - Kronestedt, Torbjörn; Marusik, Yuri M.; Omelko, Mikhail M. (Zootaxa, 2014)
The eight Palearctic species of the Pardosa nigra group are reviewed, illustrated and keyed. Two of them are redescribed: Pardosa lyrata (Odenwall, 1901) and P. paramushirensis (Nakatsudi, 1937). The former is widespread in Siberia and has also been found in Mongolia while the latter has been recorded from Japan (Honshu and Hokkaido) and Russia: the Kuril Islands (a neotype is designated from topotypic material from Paramushir Island). Pardosa fomichevi sp. n. is described from the Maritime Province (Primorye) in Russia, based on both sexes. Pardosa arctica (Kulczyński, 1916) is placed as a synonym to P. eiseni (Thorell, 1875).